A covariance-based structural equation model of structural pathways influencing the performance of village health volunteers in Kranuan District, Khon Kaen, Thailand - Ratchaneekon Khueacharee; Prasong Kitidamrongsuk; Pornanan Domthong; Uthumporn Panitanarak (Journal of Public Health and Development, 2026)
This cross-sectional study aimed to develop and test a model explaining the performance of Village Health Volunteers (VHVs) in Kranuan District, Khon Kaen Province, Thailand. VHVs are community residents selected and trained under the guidelines of the Ministry of Public Health and play a key role in community participation and access to primary healthcare services. A total of 413 VHVs were randomly selected for the study, of whom 384 completed the structured questionnaire and were included in the analysis (response rate: 92.98%). Covariance-based structural equation modeling (CB-SEM) was employed, with the measurement model first evaluated using confirmatory factor analysis (CFA) prior to testing the structural model. The final model demonstrated good fit to the data ( = 323.72, df = 286, p = 0.062; RMSEA = 0.019, 90% CI: 0.000 – 0.028; SRMR = 0.033; CFI = 0.994; TLI = 0.991) and explained 73% of the variance in VHV performance (. Empowerment and job satisfaction were directly associated with performance, whereas leadership, social networks, and work motivation were indirectly associated with performance through mediated pathways. In terms of total effects, empowerment emerged as the strongest factor associated with performance. Overall, the findings suggest that motivation, empowerment, leadership, and social networks are closely interrelated and jointly associated with VHV performance. These results highlight the importance of empowerment-oriented and motivation-supportive strategies within routine primary health care systems to strengthen VHV performance.